A interface entre cognição social e sintomas neuropsiquiátricos na esclerose múltipla remitente recorrente - Maira Cardoso Aspahan (2022)
Introduction: Multiple sclerosis (MS) causes motor and sensory deficits, neuropsychiatric symptoms and cognitive impairment. One of the cognitive domains is social cognition (SC), which refers to cognitive processes such as perception and understanding of social information, and mental inferences about the others. Studies on SC in MS are still limited and the influence of depression, fatigue and apathy on SC performance is unclear. Objective: To investigate the profile of patients with relapsing-remitting MS (RRMS) in neuropsychological tests with an emphasis on SC and to explore correlations of SC measures with depression, fatigue, and apathy. Methods: We included two groups of participants: 20 patients with RRMS (mean age = 40.15±10.15, mean schooling 15.35±1.98, 4 men/16 women, Expanded Disability Status Scale (EDSS) = 2.5±1.5) and 20 healthy controls (mean age = 40.35±10.10, mean schooling 16.3±1.9.4 men/16 women), matched for sex, age, and schooling. Patients with RRMS had no history of relapses in the last 90 days and no other neurologic severe disease. All participants were assessed with the Beck Depression Inventory, Apathy Scale, Fatigue Scale, Brief International Cognitive Assessment for MS (BICAMS), Hayling test, and semantic fluency (animals). The SC evaluation was done with the Reading the Mind in the Eyes Test, and the mini version of the Social Emotional Assessment (mini-SEA), which is composed of the emotions test (FERT) and the modified Faux-Pas test (mFP). Results: Patients with EMRR showed lower performance in semantic influence (p<0.01), processing speed (p<0.01), visual memory (p<0.01), and episodic memory (p<0.02) than healthy controls. Regarding SC scores, patients had lower performance on FERT (p<0.024), mFP (p<0.016) and Mini-SEA (p<0.02), but not on RMET. Conclusion: Patients with RRMS have SC deficits and this cognitive domain appears to be independent of depression, apathy, fatigue, episodic memory, and executive functions. The cognitive phenotype of SC-only impairment was identified in the RRMS group. More studies are to investigate the interface between SC deficits and psychiatric symptoms in MS.